Damage resistance investigation of Armox 500T and Aluminum 7075-T6 plates subjected to drop-weight and ballistic impact loads - Eyüp Yeter (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The main objective ofthis paper is to investigate damage resistance of Armox 500T and Aluminum7075-T6 plates subjected to drop-weight and ballistic impact loads.Investigating the behavior of structures under the low or the high velocityimpact loads is an important research topic. The study of materials and theircombinations provides fundamental understanding of many engineering structures.In this study, firstly drop weight and ballistic impact resistance of theArmox-500T and Al7075-T6 materials was examined. Ballistic impact analyses werecarried out using 7.62 API projectiles with an initial velocity of 800 m/s.During the drop-weight analyses, the drop of 5.5 kg weight from the 800 mmdistance was modeled. The situations at which target plates of differentthickness can be fully penetrated or not to be fully penetrated by theprojectile, the final (residual) velocities in the fully penetrated plates andthe amount of energy absorbed by the target plates were investigated. 6.72 APIprojectiles with an initial velocity of 800 m/s could not fully penetrated the10 mm Armox-500T target and 26 mm Al7075-T6 target. When drop-weight resultsare concerned, the maximum impact loads of the Armox-500T target is higher thanthe Al7075-T6, and the deformation amount is less. In addition, 10 differenthybrid models, which consist of various combination of Armox 500T and Al7075-T6materials in different thicknesses and orientations, have been defined. Thesemodels were compared with each other and models that are more resistant toballistic impact loads were determined. M4, M7, M9, and M10 models were foundto be more resistant to the ballistic impact loads than other models.